Correlation between perfluoroalkyl and polyfluoroalkyl substances and adult asthma in the NHANES - Tiankai Shan; Kai Wu; Jingxian Jiang (Medicine, 2026)
Per- and polyfluoroalkyl substances (PFAS) are pervasive organic compounds that have garnered significant attention due to their potential impacts on human health, particularly in relation to asthma, though current evidence remains limited. This study aimed to examine the association between PFAS exposure and adult asthma using a sample of 7106 participants aged 20 years and older from the NHANES survey, spanning 2003 to 2018. Survey-weighted multivariable logistic regression models, subgroup analysis, weighted quantile sum and Bayesian kernel machine regression models were employed to probe the relationship between PFAS and asthma. In the multivariable logistic regression analysis, higher log10-transformed perfluorooctane sulfonic acid (PFOS) and PFNA concentrations were significantly associated with lower odds of asthma (PFOS: OR = 0.76, 95% CI: 0.61–0.96; PFNA: OR = 0.77, 95% CI: 0.60–0.99). The inverse link between PFAS co-exposure and asthma incidence persisted across multi-pollutant models, weighted quantile sum regression, and Bayesian kernel machine regression models, with PFOS emerging as the primary negative influencer. In conclusion, this study highlights PFAS exposure is inversely associated with asthma risk in adults.